Fluctuations of Estimated Glomerular Filtration Rate Outside Kidney Disease Improving Global Outcomes Diagnostic Criteria for Acute Kidney Injury in End-Stage Liver Disease Outpatients and Outcome Postliver Transplantation. Issue 1 (January 2018) - Fiacco, Federica; Melandro, Fabio; Umbro, Ilaria; Zavatto, Assunta; Cappoli, Andrea; Poli, Edoardo; Ginanni Corradini, Stefano; Merli, Manuela; Tinti, Francesca; Nofroni, Italo; Berloco, Pasquale B.; Rossi, Massimo; et al.
Abstract : Background: Renal dysfunction in end-stage liver disease (ESLD) results from systemic conditions that affect both liver and kidney with activation of vasoconstrictor systems. In this setting, estimated glomerular filtration rate (eGFR) may undergo variations often outside Kidney Disease Improving Global Outcomes criteria for acute kidney injury (AKI) diagnosis, whose meaning is not clear. The aim of this study was to evaluate eGFR variations in ESLD outpatients listed for liver transplant (liver Tx) and the association with post-Tx outcome. Methods: Fifty-one patients with ESLD were retrospectively evaluated from listing to transplant (L-Tx time), intraoperatively (Tx time), and up to 5 years post-Tx time. Variations between the highest and the lowest eGFR occurring in more than 48 hours, not satisfying Kidney Disease Improving Global Outcomes guideline, were considered as fluctuations (eGFR-F). Fluctuations of eGFR greater than 50% were defined as eGFR drops (DeGFR). Early graft dysfunction, AKI within 7 days, chronic kidney disease, and short- and long-term patient survivals were considered as outcomes. Results: All patients presented eGFR-F, whereas DeGFR were observed in 18 (35.3%) of 51 (DeGFR+ group). These patients presented higher levels of Model for End-stage Liver Disease score, pre-Tx bilirubin and significantly greater incidence of post-Tx AKI stages 2 to 3 compared with patients without drops (DeGFR−). DeGFR was the only independent predictive factor of the occurrence of post-Tx AKI. The occurrence of AKI post-Tx was associated with the development of chronic kidney disease at 3 months and 5 years post-Tx. Conclusions: Drops of eGFR are more frequently observed in patients with a worse degree of ESLD and are associated with a worse post-Tx kidney outcome.